Utilization of Bioflok on Vaname Shrimp (litopenaeus vannamei) Cultivation - Sudirto Malan; M. Abjan Fabanjo (Jurnal Biologi Tropis, 2022)
Vaname shrimp (Litopenaeus vannamei) cultivation is a promising business. Biofloc technology is an alternative to solve the problem of intensive aquaculture waste. Biofloc technology is able to provide additional protein feed for cultivated animals so that it can increase growth, besides that this technology is also effective in reducing inorganic nitrogen waste from leftover feed and manure. The purpose of this study was to determine the effect of different doses of biofloc on the growth rate of Vannamei Shrimp (Litopenaeus vannamei) and the effect of different doses of biofloc on the survival of Vannamei shrimp (Litopenaeus vannamei). The method used is the experimental method. Experiments carried out in this study were to determine the effect of biofloc with different doses on the growth rate of white shrimp. The study design was a completely randomized design with four treatments and three replications, treatment A (commercial feeding without the addition of biofloc), treatment B (giving commercial feed with the addition of 15 mL of biofloc) C (feeding commercially with the addition of 20 mL of biofloc). ) and D (addition of 20 mL of biofloc without commercial feeding). Vaname shrimp seed stocking density for each treatment amounted to 15 fish/container. The application of biofloc had a significant effect on the growth rate of daily specific average weight and the increase in length of Vaname shrimp seeds (p<0.05). The highest growth rates in weight and length were obtained in treatment B (commercial feeding with the addition of 10 mL of biofloc) of 0.55ÃÂ±0.02%/day and 3.7ÃÂ±0.01 cm, respectively. The addition of biofloc did not show any significant effect on the survival rate of Vaname shrimp fry (p>0.05).